Intraoperative Neuromonitoring for Pediatric Pelvic Tumors - Crocoli, Alessandro; Martucci, Cristina; Randi, Franco; Ponzo, Viviana; Trucchi, Alessandro; De Pasquale, Maria Debora; Marras, Carlo Efisio; Inserra, Alessandro (Frontiers in Pediatrics, 2022)
Background: Tumors of the pre-sacral and sacral spaces are a rare occurrence in children. Total tumor excision is required due to the significant risk of relapse in the event of partial surgery, but the surgical procedure may lead to postoperative problems such as urinary, sexual, and anorectal dysfunctions. Intraoperative Neurophysiological Monitoring (IONM) has gained popularity in recent years as a strategy for preventing the onset of neurologic impairments by combining several neurophysiological techniques. The aim of our study is to describe the experience of Bambino Gesù Children’s Hospital in the use of IONM in pediatric pelvic surgery. Materials and methods: Data of patients treated for pelvic malignancies at Bambino Gesù Children’s Hospital from 2015 to 2019 were retrospectively collected. All patients were assessed from neurologic and neuro-urologic point of view at different time-points (before and immediately after surgery, after 6 months and 1 year follow-up). They were all monitored during surgical procedure using multimodal IONM including Transcranial Motor Evoked Potentials (tcMEP), Free-run and triggered Electromyography (EMG), Pudendal somatosensory evoked potentials (pSSEP) and Bulbo-Cavernosus Reflex (BCR). Results: During the study period, ten children underwent pelvic tumor removal at our Institution. In all cases, intraoperative neurophysiological recordings were stable and feasible. The preservation of neurophysiological response at the same intensity during surgical procedure correlated with no new deficits for all neurophysiological techniques. Discussion: Although the impact of the IONM on surgical strategies and clinical follow-up is unknown, this preliminary experience suggests that the appropriate use of several neurophysiological techniques can influence both the radicality of pelvic tumor removal and the neurological and urological outcome at clinical follow-up. Finally, because of the highly complex anatomy and inter-individual variances, this is especially useful in this type of surgery.